Réponses

2012-12-10T21:26:26+01:00

a) 5x-10 =2x+x+6 = 5x-2x-x =6+10

= 2x =16  x = 16/2 = 8

 

b) 12 -5x+9 = 4x+3

= -5x-4x = 3-12

= -9x = -9 donc x = 1

 

c) 5 +6x+6 = 6-4x-1

= 6x+4x =6-1-6-5

= 10x = -18 x = -18/10 = -9/5

2012-12-10T21:28:11+01:00

5(x-2)=2x+(x+6)

5x - 10 = 2x + x + 6

5x - 10 = 3x + 6 

2x -10 = 6

2x = 16 
x = 16/2
x = 8

12 -(5x -9)=4x+3
12 -5X + 9 = 4x +3

-5x +21 = 4x + 3
-9x +21 = 3
-9x = -18
x= 18/9 = 2 

5+3(2x+2)=6-4(x+1)

5 + (6x + 6) = 6 -(4X + 4)
5 + 6X + 6 = 6 -4X -4
6X + 11 = -4X + 2
10x + 11 = 2
10x = -9
x = -9/10